Estudos de linguística histórica: mudança e estandardização - Clarinda de Azevedo Maia (Investigação, 2019)
This book contains a set of different works unified by a common theme and by a common analysis approach: historical linguistics and the processes of linguistic change and standardisation. The volume combines two types of contributions, providing contact with research directions and research projects being conducted in different parts of the world. Some texts discuss theoretical and methodological subjects currently considered in linguistic studies, particularly in the field of historical linguistics. Other chapters aim to study the change of linguistic structures and linguistic usages. In these cases, detailed analysis of empirical and diversified data is provided. Finally, some contributions of this volume take codificatory work over Portuguese as corpus. Such data supports research on the knowledge of the ancient language and provides the researcher with relevant elements for the comprehension and clarification of the standardisation processes, a phenomenon that usually accompanies the elaboration of languages.